2021
DOI: 10.1186/s12864-021-07797-7
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling of developing leaf and shoot apices to reveal the molecular mechanism and co-expression genes responsible for the wheat heading date

Abstract: Background Wheat is one of the most widely planted crops worldwide. The heading date is important for wheat environmental adaptability, as it not only controls flowering time but also determines the yield component in terms of grain number per spike. Results In this research, homozygous genotypes with early and late heading dates derived from backcrossed progeny were selected to conduct RNA-Seq analysis at the double ridge stage (W2.0) and androgyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Six seedlings were separately sampled at 0 h, 5 min, 0.5 h, 1 h, 6 h, and 12 h after application of heat stress. We selected three genes from OG0272, OG0283, and OG2039 for RT-qPCR, which was performed as described previously ( Yang et al., 2021 ). The primer sequences used in this research are listed in Supplemental Table 10 .…”
Section: Methodsmentioning
confidence: 99%
“…Six seedlings were separately sampled at 0 h, 5 min, 0.5 h, 1 h, 6 h, and 12 h after application of heat stress. We selected three genes from OG0272, OG0283, and OG2039 for RT-qPCR, which was performed as described previously ( Yang et al., 2021 ). The primer sequences used in this research are listed in Supplemental Table 10 .…”
Section: Methodsmentioning
confidence: 99%
“…Data processing and analysis were performed according to the methods described in Yang et al . (2021).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we observed that the gsk3 mutant shows late heading and flowering (Figure 1A–C), as mentioned in a previous report (Cheng et al, 2020). Our earlier transcriptome analysis (Yang et al, 2021) showed that GSK3 is highly expressed in the shoot apex and leaves of wheat variety YZ4110 at the W2.0 and W3.5 stages (Figure S1). This result raises the interesting question of how GSK3 regulates the heading and flowering dates of wheat.…”
Section: Figurementioning
confidence: 96%